Husbandry and methodology for assessing learning and memory in the juvenile life stage of octopus - Shaquilla Hamlett (MethodsX, 2024)
The purpose of this project was to use modified methodology and new approaches to determine whether the California two-spotted octopus (Octopus bimaculoides) shows evidence of higher cognitive function as juveniles. This species’ cognitive ability was assessed in ∼4 month old octopus using a food preference test and a learning test (ability to recognize a habitat created from 3D printed rocks and navigate to its hidden food source). Methods for determining associative learning for this species were developed. In addition, potential enhancements to future O. bimaculoides husbandry and study design are discussed. • Enrichment and care methodology for juvenile cephalopods from hatchling to juvenile • In the article we discuss new approaches for studying associative learning, spatial learning, and food preference that can be adapted for various species of cephalopods, and the usage of 3D printing as a habitat re-creation tool in aquaria • We introduce histology methodology for observing and comparing brain development in juvenile cephalopods